Alhagi: A Plant Genus Rich in Bioactives for Pharmaceuticals. (24th September 2014) - Muhammad, Gulzar; Hussain, Muhammad Ajaz; Anwar, Farooq; Ashraf, Muhammad; Gilani, Anwarul‐Hassan
<x xml:space="preserve">Abstract</x> Alhagi, a plant genus from family Fabaceae, is widely distributed in many countries of Asia, Australia and Europe. Commonly known as camel thorn, Alhagi has many species famous for feed and folk medicinal uses. Different species of Alhagi such as Alhagi pseudalhagi, A. graecorum, A. sparsifolia, A. kirgisorum, A. maurorum, A. camelorum and A. persarum have been explored for their antioxidant potential and nutritive value along with various medicinal properties. A wide array of pharmacologically active secondary metabolites such as flavonoids, alkaloids (alhacidin and alhacin), steroids, pseudalhagin A, phospholipids and polysaccharides have been reported from different parts of Alhagi species. A broad range of biological activities such as antioxidant, cardiovascular, anti‐ulcer, hepatoprotective, antispasmodic, antidiarrheal, antinociceptive, antipyretic, anti‐inflammatory, anti‐rheumatic, antibacterial and antifungal have been ascribed to different parts of Alhagi. In addition, Alhagi plants are also valued as a rich source of digestible protein and important minerals. This review focuses on the medicinal applications and detailed profile of high‐value bioactive phytochemicals along with pharmacological attributes and therapeutic potential of these multi‐purpose plants. Copyright © 2014 John Wiley & Sons, Ltd.